Adult child migration and elderly parental health in rural China. Issue 4 (7th November 2016) - Chang, Fang; Shi, Yaojiang; Yi, Hongmei; Johnson, Natalie
Abstract : Purpose: The purpose of this paper is to evaluate the effect of adult children migration on the health status of elderly parents. Increased labor migration in developing countries that lack adequate social security systems and institutionalized care for the elderly is a phenomenon that is important to understand. When their adult children go away to work, it is not clear what effect there will be on "left-behind" elderly parents. Design/methodology/approach: This study employs nearly nationally representative data from five provinces, 25 counties, 101 villages and 2, 000 households, collected from two waves of data in 2007 and 2011. This sample comprises a subset of households which include both elderly individuals (above 60 years old) and their grown (working-aged) children in order to estimate the impact of adult child migration on the health of elderly parents in rural China. Findings: This study finds that adult child migration has a significant positive impact on the health of elderly family members. Practical implications: These findings are consistent with the explanation that migration raises family resources, which in turn may contribute to better health outcomes for elderly household members. Originality/value: This is the first paper to attempt to identify the relationship between household migration and the health of elderly parents within the Chinese context.